Usability Studies of e-Government Website (HALALJAKIM) - Ibrahim, Azizah (Universiti Teknologi PETRONAS, 2007)
The aim of this project is to study and analyze why it is Human Computer Interface is very important as a guideline to build a website especially in Government sectors. Guideline, principles and theories which can provide remedies and medicine for these problems have matured in recent years. The major discussion of this study is to improve the government website onfocusing the interface design. This paper will begin with a discussion about the background study of e-government website. The problem statement and scope of studies will be discussed after that. Following will be the literature review and two major part of methodology which are research methodology and design methodology. Next, the results and discussion part will be discussed about the finding of this project. Lastly, the conclusion and recommendation will be discussed for further improvement in the future.